Services and Manufacturing Linkages : An Empirical Analysis for Lao PDR - World Bank Group (World Bank, Washington, DC, 2016)
This report seeks to shed light on the ways in which the services sector has contributed to Lao PDR’s competitiveness and integration into the global marketplace. It focuses on two complementary roles that the services sector plays: first, as an avenue for export diversification and growth and, second,by providing inputs into other productive sectors of the economy, such as the manufacturing sector. As economies grow, the importance of the services sector generally increases, but its role as an enabler of other sectors of the economy in moving up the value chain is frequently overlooked. However, the services sector is critical in raising competitiveness of these other sectors to boost growth and create better quality jobs. The main policy recommendations that emerge from this report are aimed at increasing competition in the services sector, reducing distortive regulations, and opening up the sector to foreign participation, building up skills, both at the individual and at the firm level, and investing in hard and soft infrastructure to promote the development of the sector.